Carbon Catalysts for Electrochemical CO2 Reduction toward Multicarbon Products. Issue 24 (1st May 2022) - Pan, Fuping; Yang, Xiaoxuan; O'Carroll, Thomas; Li, Haoyang; Chen, Kai‐Jie; Wu, Gang
Abstract: Electrochemical CO2 reduction offers a compelling route to mitigate atmospheric CO2 concentration and store intermittent renewable energy in chemical bonds. Beyond C1, C2+ feedstocks are more desirable due to their higher energy density and more significant market need. However, the CO2 ‐to‐C2+ reduction suffers from significant barriers of CC coupling and complex reaction pathways. Due to remarkable tunability over morphology/pore architecture along with great feasibility of functionalization to modify the electronic and geometric structures, carbon materials, serving as active components, supports, and promoters, provide exciting opportunities to tune both the adsorption properties of intermediates and the local reaction environment for the CO2 reduction, offering effective solutions to enable CC coupling and steer C2+ evolution. However, general design principles remain ambiguous, causing an impediment to rational catalyst refinement and application thrusts. This review clarifies insightful design principles for advancing carbon materials. First, the current performance status and challenges are discussed and effective strategies are outlined to promote C2+ evolution. Further, the correlation between the composition, structure, and morphology of carbon catalysts and their catalytic behavior is elucidated to establish catalytic mechanisms and critical factors determining C2+ performance. Finally, future research directions and strategies are envisioned to inspire revolutionary advancements. Abstract : Carbon‐based catalysts have shown great promise for tuning reaction pathways and the local reaction environment for electrocatalytic CO2 reduction, offering effective solutions to steer valuable multicarbon product evolution. This review provides critical insights and perspectives on design principles, catalytic mechanisms, and future research directions to inspire the rational design of advanced carbon materials for converting CO2 into value‐added feedstocks.